Analisis Karakteristik Fluida dan Estimasi Temperatur Reservoir menggunakan Geoindikator Na-K-Mg di Kecamatan Tompaso Baru - Tesalonika Lontoh; Heindrich Taunaumang; Jeferson Polii (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2022)
Geothermal is a source of thermal energy contained in hot water, rock, water vapor, and other gases and minerals that are genetically inseparable from a geothermal system. This energy comes from heating water and rocks and other elements contained in geothermal energy stored in the earth's crust. Energy needs are increasing, various efforts are made to take advantage of the potential that exists in Indonesia, one of which is geothermal potential. Geothermal energy is a renewable natural resource with high potential and is one of the preferred energy sources in energy diversity. The existence of geothermal sources, marked by the presence of geothermal manifestations emerging to the surface, one of which is in Tompaso Baru District. The fluid samples were then tested in the laboratory, then data processing was carried out using the fluid geochemical method in the form of calculating the percentage of the Na-K-Mg geoindicator to determine the type of fluid and a geothermometer to determine the estimated reservoir temperature. By using the calculation of the percentage of chemical content from the laboratory test results Na/1000+K/100+√Mg and plotting a ternary diagram of a partial equilibrium waters type of geothermal fluid, namely a condition where the fluid has partially changed so that it is not fully in equilibrium, and calculations using a silica geothermometer the estimated reservoir temperature is 191.1078ºC, which is the type of reservoir with medium temperature.